Konsep Dasar Administrasi Pendidikan Berbasis Learning Era Society 5.0 - Vica Aulia Zetra; Lailatul Rahmi; Ahmad Sabri; Rully Hidayatullah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Educational Administration is an integral part of the education system that combines the principles of administration with educational practices to achieve effective and efficient learning outcomes. The concept of educational administration involves processes such as planning, organizing, directing, and supervising educational activities with the goal of enhancing educational quality. This concept includes various functions such as managerial, technical, analytical, interpersonal, and managerial administration that support educational management. Educational administration covers several important aspects such as student administration, curriculum, educational staff, facilities and infrastructure, finance, and community relations.In the era of Society 5.0, introduced by Japan in 2017, there is an integration of advanced technologies such as IoT, AI, and big data into various aspects of life, including education. Society 5.0 aims to create an inclusive and intelligent society by utilizing technology to improve the quality of learning and educational management. This concept focuses on leveraging technology to simplify human life, bridge gaps, and provide solutions that are more adaptive to the needs of individuals and society. The combination of educational administration with the principles of Society 5.0 offers opportunities to optimize the education system, increase efficiency and effectiveness, and address the challenges faced in the rapidly evolving digital era.